Passion to Profession: A review of Passion fruit Processing - Biswas, Srishti; Mishra, Ritesh; Bist, Ankur Singh (Aptisi Transactions On Technopreneurship (ATT), 2021)
Passion fruit (Passiflora edulis) is a nutritious tropical fruit belongs to the family Passifloraceae. The purple passion fruit is local from southern Brazil through Paraguay to northern Argentina. India, for a long time, has appreciated a moderate collect of purple passion fruit in the Nilgiris in the south and in various parts of northern India. The Passion fruit has good amount of antioxidants, flavanoids, anti- inflammatory, anti- bacterial, anti- fungal and anti- ageing properties. This fruit has huge economical importance as all the parts of this fruit (seed, peel, flower, pulp) are rich in medicinal and therapeutic properties. The fruit is a fantastic wellspring of dietary fiber, nutrient, Vitamin C and Vitamin A. Being a decent laxative, it likewise secures the colon mucosa by diminishing openness time to harmful substances in the colon and clearing off the malignant growth causing poisonous substances from the colon. Passion fruit has several medical advantages and hence require diverse processing and preservation methods. Here we are going to review portion of these methods.